The event study in international business research: Opportunities, challenges, and practical solutions - Eden, Lorraine; Miller, Stewart R.; Khan, Sarfraz; Weiner, Robert J.; Li, Dan (Journal of International Business Studies, 2022)
The event study or event study method (ESM) is an empirical technique for capturing investors’ reaction to an event affecting one or more publicly traded firms. The ESM has been little employed in international business (IB) research despite its frequency in accounting, economics, and finance; for example, only two percent of the empirical articles in JIBS over 1970–2019 include an event study. While this scarcity could indicate a lack of demand, we argue that the field of IB studies offers many interesting and important research opportunities for an event study. We believe that the challenges arise primarily from the supply side, because conducting an event study involves overcoming a variety of data and analytical hurdles. We examine these methodological challenges and offer practical solutions designed to encourage adoption of the ESM. An online appendix with coding and examples provides additional resources.